Ethno-zootechnics from the perspective of dairy farmers in the brazilian cerrado - Bráulio, Roberta de Castro; Redin, Ezequiel; Pereira, Anderson Alvarenga; Mota, Diego Azevedo; Melo, Thiago Vasconcelos (Revista de Ciências Agroveterinárias, 2023)
Considering the valuable environmental and cultural heritage existing in the world in the context of agribusiness, it is possible to highlight the role of ethno-zootechnics as an important new tool for understanding these values, the rescue and generational transmission of livestock knowledge are relevant. Given this, the objective was to understand the perception of milk producers from the Ethno-zootechnical perspective. Through a semi-structured script, questionnaires were carried out with 41 interviewees and representatives of dairy farms to register the relevance of basic cultural knowledge associating them with social, economic and social environmental development. Cluster analysis was carried out using the hierarchical method. It was concluded that part of the dairy farmers located in the Northwest region of Minas Gerais state, the man/animal relationship is important, with traits of affection and utility. The transmission of traditional knowledge of the dairy activity is important, and that they believe that scientific and traditional knowledge can be beneficial in rural activity.